Improving Public Policy for Children: A Vote for Each Child - Robert H. Pantell; Maureen T. Shannon (Intergenerational Justice Review)
Changes in social policy in the United States (US) over the past four decades have provided health insurance for 100 percent of persons over age 65 and decreased poverty for this group while the number of children in poverty has risen and ten million are uninsured. is increasing intergenerational inequity reflects political decisions where children lack a voice. The purposes of this paper are to: 1) summarize, from the fields of ethics, government, law, social welfare and public health, current thinking about enfranchisement of children; 2) review the evolution of voting and representation in the US and identify misperceptions about barriers to equitable representation of children; 3) discuss the legal basis for children being regarded as adults and adult proxy decision making for children; and 4) suggest strategies to stimulate an equitable system of child representation by altering our current system of voting.